Power Shifts, Emigration, and Population Sorting - Michaël Aklin; Vera Z. Eichenauer (Center for Economic Studies and ifo Institute (CESifo), 2022)
We investigate the consequences of a peaceful shift of power from one social group to another. Theoretically, we show that an individual's decision to stay put or migrate depends on the difference between the political preferences of groups and the change in tax. Empirically, we use the case of the unexpected creation of the Canton of Jura in Switzerland, which witnessed a power shift from German to French speakers in the 1970s. We find robust evidence supporting the model's predictions using data at the municipal and individual levels. Our research sheds light on population sorting in the shadow of power transitions.
Keywords: H31; H77; D72; J15; 330; social identity; status displacement; migration; federalism; secession